Development of a Molecular Tool for Identification of a New Neopestalotiopsis sp. Associated with Disease Outbreaks on Strawberry - Kaur, Harleen (Plant disease, 2023)
A new Neopestalotiopsis sp. was recently reported causing outbreaks of leaf spot and fruit rot on strawberry in Florida, Georgia, and South Carolina. In contrast to other Pestalotiopsis pathogens, the new species appears more aggressive and destructive on strawberry. Current chemical options for management are disease suppressive at best, and affected growers have been experiencing major yield losses. In this study, we developed a molecular method based on polymerase chain reaction/restriction fragment length polymorphism (PCR/RFLP) for identification of the new Neopestalotiopsis sp. from strawberry. Isolates of the new Neopestalotiopsis sp. collected in Florida; isolates of N. rosae, N. honoluluana, N. ellipsopora, N. saprophytica, N. samarangensis, and P. rhododendri; and isolates from South Carolina suspected to be the new Neopestalotiopsis sp. were included in this study. This method is based on PCR amplification of a β-tubulin gene fragment using a previously published set of primers (Bt2a and Bt2b), followed by use of the restriction enzyme BsaWI. The enzyme cuts the PCR product from the new Neopestalotiopsis sp. twice, yielding fragments of 290 base pairs (bp) and 130 and 20 bp in size, whereas fragments from other species are only cut once, yielding fragments of 420 and 20 bp. This method will aid research labs and diagnostic clinics in the accurate and fast identification of the aggressive Neopestalotiopsis sp. variant from strawberry